Severity of the cardiac impairment determines whether digitalis prolongs or reduces survival of rats with heart failure due to myocardial infarction - Santos, Alexandra Alberta dos [UNIFESP] (2013)
Background: the aim of the present study was to evaluate if the influence of digitalis on survival depends on the severity of cardiac dysfunction in heart failure (HF).Methods and results: Doppler echocardiogram (DE) parameters were analyzed in 84 Wistar control (C) and 80 Wistar rats treated with 0.1 mg/100 g/day of digitoxin (D) five days after coronary occlusion. the de variables correlated with the survival of the animals were: myocardial infarction size, left chamber dimensions, fractional area change and E/A ratio. the animals were observed for up to 280 days. Mortality was worsened in rats in the D group with a myocardial infarction (MI) < 37% and with better de predictors of survival. Digitoxin was found to prolong survival in rats with an MI >= 37% and worse de predictors.Conclusion: for the first time our study has shown experimentally that the action of digitalis glycosides can positively or negatively influence survival during treatment of HF. It prolongs survival of those in advanced state and compromises survival when there is less severity of the disease. in fact, the greater benefits occur when digitoxin was used in heightened ventricular dilatations and worse ventricular performance. (c) 2011 Elsevier Ireland Ltd. All rights reserved.